2011
DOI: 10.1590/s0004-28032011000100005
|View full text |Cite
|
Sign up to set email alerts
|

Achalasia in the elderly patient: a comparative study

Abstract: -Context -Achalasia is a primary esophageal motor disorder secondary to the degeneration of ganglion cells of the inhibitory intramural myenteric plexus. It affects both sexes similarly and has two peaks of incidence, one in the 3rd to 4th decades of life and the other after 60 years of age. The effect of age on esophageal motility of patients with achalasia is not well known. Studies have shown that healthy older people, when compared to the young, have: a) a lower number of ganglion cells in the intramural m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
0
9
0
5
Order By: Relevance
“…Achalasia, a primary esophageal motor disorder secondary to the degeneration of ganglion cells of the inhibitory intramural myenteric plexus of unknown etiology, involves hypertension and poor relaxation of the body of the esophagus and the lower esophageal sphincter, affects both sexes and all ages, and has two peaks of incidence, one in the third to fourth decades of life and the other after 60 years of age . Because of the slow progression of its symptoms and low incidence (~1–2 per 100,000 per year), achalasia may remain undiagnosed for years .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Achalasia, a primary esophageal motor disorder secondary to the degeneration of ganglion cells of the inhibitory intramural myenteric plexus of unknown etiology, involves hypertension and poor relaxation of the body of the esophagus and the lower esophageal sphincter, affects both sexes and all ages, and has two peaks of incidence, one in the third to fourth decades of life and the other after 60 years of age . Because of the slow progression of its symptoms and low incidence (~1–2 per 100,000 per year), achalasia may remain undiagnosed for years .…”
Section: Discussionmentioning
confidence: 99%
“…Older adults with idiopathic esophageal achalasia have similar clinical and manometric presentations but less‐severe chest pain than younger individuals . Achalasia of older adults is significantly associated with greater risks of pulmonary complications, malnutrition, and gastroesophageal cancer and higher prevalence of Chagas disease in South American countries . Owing to chronic microaspiration, individuals with achalasia may have respiratory symptoms of nocturnal cough, poor pulmonary function in the form of restrictive or obstructive airway disease, and abnormal findings on high‐resolution chest CT, including tracheobronchial compression by the dilated esophagus, pulmonary nodules, ground‐glass opacities, fibrosis, consolidations, air‐trapping, and bronchiectasis .…”
Section: Discussionmentioning
confidence: 99%
“…In order to resolve this disagreement we examined ganglionic cell number to myenteric plexus volume ratio and confirmed the very similar percentage of cell loss, without significant reduction of plexus itself during aging. In the previously published clinical reports [11,19,28,29] authors suggested that motility disorders in the gastrointestinal system are related to the aging and they can be caused by some systemic diseases. We confirmed that aging has a significant deleterious effect on the neuronal cell population in the whole oesophagus, not only in the sphincters region.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to an inability of muscle contraction in the distal two-thirds and concomitant failure of relaxation of the lower oesophageal sphincter which can cause retention of food bolus [3, 4]. These patients present with a well-recognised and long standing history of dysphagia, particularly to liquids.…”
Section: Discussionmentioning
confidence: 99%